2019
DOI: 10.1111/edt.12496
|View full text |Cite
|
Sign up to set email alerts
|

How does orofacial trauma in children affect the developing dentition? Long‐term treatment and associated complications

Abstract: Each year, millions of children are injured and live with the consequences of those injuries. Through infancy and childhood, orofacial trauma caused by falls or being struck by or against objects occurs in children. The long‐term implications on the developing permanent teeth are little known, even when the oral region is the second most frequently injured body area in children under 6 years of age. During this period, the developing permanent teeth may be directly involved after trauma, causing mild to severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 21 publications
(31 reference statements)
0
20
0
3
Order By: Relevance
“…During the dental trauma, the majority of injuries involves the anterior teeth and usually affects only the tooth that suffered the impact [6,7]. It is well reported that during a trauma, the biomechanical response from maxillofacial structures involves the enamel, root dentin, periodontal ligament, and surrounding bone at the load dissipation [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the dental trauma, the majority of injuries involves the anterior teeth and usually affects only the tooth that suffered the impact [6,7]. It is well reported that during a trauma, the biomechanical response from maxillofacial structures involves the enamel, root dentin, periodontal ligament, and surrounding bone at the load dissipation [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, awareness of the importance of mouthguards did not mean its usage by the athletes, except by hockey players [10]. In this sense, the literature is very concise regarding the preventive effect of mouthguard device to reduce the incidence of maxillofacial injuries during contact activities [4,[7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Das Hauptproblem liegt dabei in der möglichen Schädigung der zweiten Dentition. Vor allem bei Intrusionsund Avulsionsverletzungen kann es zu primären Schädigungen des Zahnkeims kommen [6]. Dabei spielt vor allem der Mineralisationsgrad des Zahnkeims, die Verletzungsart und die Krafteinwirkung für die Prognose eine entscheidende Rolle [7].…”
Section: Epidemiologieunclassified
“…So steigt die Wahrscheinlichkeit einer Kronenfehlbildung bei unter 2-Jährigen und Dilazerationen oder Durchbruchstörungen (▶ Abb. 16) bleibender Zähne bei unter 5-Jährigen vor allem nach Intrusions-oder Avulsionsverletzungen [6].…”
Section: Komplikationen Und Folgeschädenunclassified
“…The tooth morphology of the population of Northeast Asian countries, including Mongolia, Korea, and Japan, is distinct, such as shovel-shaped teeth and smaller R/C ratios [ 6 , 7 , 8 , 9 ]. The etiologic factors of SRA remain largely unknown, but SRA occurs when the root formation is affected by genetic factors [ 10 , 11 ] or environmental factors such as trauma, chemotherapy, and radiation therapy [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%